PROSTHETICS IN CANCER PATIENTS WITH ORBITAL DEFECTS - A. A. Kulakov; V. M. Chuchkov; E. G. Matyakin; I. S. Romanov; A. A. Akhundov; A. M. Mudunov; S. P. Fedotenko; N. N. Fedotov; S. O. Podvyaznikov; M. A. Kropotov; O. A. Zharkov; M. V. Chuchkov; et al. (Опухоли головы и шеи, 2015)
Orthopedic treatment was performed in 53 patients with postoperative defects in the orbital area during 1969–2012. The developed practical guidelines could improve the cosmetic aspects of ectoprostheses, their fixation, and quality of life in the patients.